Improving Reading Comprehension Skills of Students with Learning Difficulties through the Problem-Based Learning Model in Grade 5 Primary School - Goran, Elisabeth Nyora; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Reading comprehension is a crucial skill in primary education, yet many students—especially those with learning difficulties—struggle to achieve mastery. Traditional, lecture-based instruction often fails to address their diverse cognitive and motivational needs. This study aims to improve reading comprehension among fifth-grade students with learning difficulties through the implementation of the Problem-Based Learning (PBL) model. Employing a Classroom Action Research (CAR) approach with three iterative cycles, the research was conducted at SDN Bukit Makmur, East Kutai, involving 20 students. Data collection involved observations, pre- and post-tests, and documentation. Instructional interventions were designed to align with the phases of PBL, encouraging students to engage in contextual problem-solving and collaborative learning. The findings demonstrated progressive improvements across all three cycles. Student activity scores increased from an average of 2.88 to 3.67, while teacher activity scores improved from 3.25 to 3.75. Notably, post-test results revealed an increase in mastery from 15% to 100%, with all five students identified as having learning difficulties successfully achieving competency. These results indicate that the PBL model effectively fosters both cognitive engagement and academic achievement. The study underscores the importance of reflective, student-centered instruction in supporting inclusive literacy development and offers practical insights for educators seeking to address comprehension gaps in diverse classroom settings.